DETERMINING FACTORS FOR MODERATING LEVERAGE BOND RATINGS - Sari Bulan Tambunan; Warsani Purnama Sari; Alfriado Leonard Noprian Dolok Saribu Dolok Saribu; Ahmad Prayudi; Dhian Rosalina; Yusnaini Yusnaini (Jurnal Akuntansi Trisakti, 2023)
This study aims to determine the factors that influence the policy of imposing bond rates with leverage as a moderating variable. The population in this study were 55 companies listed on the Indonesia Stock Exchange and registered at PT. Pefindo successively during the 2018-2020 period using a sampling technique, namely census sampling where the entire population is sampled. The test results show that profitability and audit quality have positive effect on bond ratings. Liquidity variable have no effect on rating assignment, and also financial flexibility and company size have no effect on rating assignment. Leverage in this study is only able to moderate the effect of profitability and audit quality on bond ratings. Meanwhile, liquidity, financial flexibility and company size cannot be moderated by leverage on bond ratings of companies listed on the IDX and Pefindo during the 2018-2020 period.